Perdagangan Perempuan dengan Dalih Perkawinan - Sabirin Sabirin (Raheema, 2017)
The emergence of trafficking cases of women is a direct result of the inadequacy of society due to poverty and other causes. The modus operandi of this trade is varied, but the mode of trafficking of women under the pretext of marriage is considered the most dangerous in the case of trafficking in women. Such cases have long been happening and are still growing today. The occurrence of female trafficking cases with the modus operandi of marriage involves intermediaries (brokers) that bring together men with women who are generally low-income (poor) and low-educated families. This paper will discuss what is really the trafficking of women, the factors that influence the occurrence of women's handling with the pretext of marriage, the form of victim protection and prevention efforts that can be done.